Nurses descriptions of changes in cognitive function in the acute care setting - Hare, Malcolm; McGowan, Sunita; Wynaden, Dianne; Speed, G.; Landsborough, Ian (Australian Nursing Federation, 2008)
To describe nurses' documentation of cognition and behavioural changes in patients in acute care settings. Hospitalised patients often present with multiple co-morbidities including declining levels of cognitive functioning and this is particularly so for older people. Many older people will experience a delirium during hospitalisation. While prevention or prompt management of delirium is paramount to providing quality care, research suggest that health professionals regularly fail to differentiate between delirium and other cognitive changes in hospitalised patients. A total of 1209 patients were surveyed over the four audit days with 183 patients (15%) being identified as confused. 'Confusion" was the most common descriptor used by nurses to describe cognitive and behavioural changes; in many cases it was the only term used. Many of these changes were indicative of delirium. Little use by any health professional of cognitive screening tools were found.Cognitive and behavioural changes are a common problem in hospitalised patients who are elderly. The use of the term confusion to describe a range of cognitive and behavioural changes is a barrier to accurate identification of delirum, which is often the first indicator of serious underlying illness.